A Modified Miniscope System for Simultaneous Electrophysiology and Calcium Imaging in vivo - Wu, Xiaoting; Yang, Xiangyu; Song, Lulu; Wang, Yang; Li, Yamin; Liu, Yuanyuan; Yang, Xiaowei; Wang, Yijun; Pei, Weihua; Li, Weidong (Frontiers in Integrative Neuroscience, 2021)
Miniscope system is one of the calcium imaging tools with small size, lightweight, and can realize deep-brain calcium imaging not confined to the cerebral cortex. A combination of calcium imaging and electrophysiology recording has been an efficient method for extracting high temporal-spatial resolution signals in the brain. In this paper, A particular electrode probe was developed and assembled on the lens to modify the miniscope system. The electrode probe can be tightly integrated into the lens of the miniscope without increasing the volume, weight, and implantation complexity. In vivo tests verified that the proposed modified system had realized the simultaneous recording of calcium (Ca2+) signals and local field potential (LFP) signal in the hippocampus CA1 region of an adult mouse.